Food waste compost as an organic nutrient source for the cultivation of Chlorella vulgaris. (November 2018) - Chew, Kit Wayne; Chia, Shir Reen; Show, Pau Loke; Ling, Tau Chuan; Arya, Shalini S.; Chang, Jo-Shu
Highlights: Utilization of food waste compost as an organic medium for microalgae cultivation. Evaluation of microalgae growth and biochemical composition using organic medium. Combination of up to 50% organic medium showed higher biomass yield. Combination of up to 35% organic medium showed higher lipid and protein content. Replacement of inorganic medium with organic medium is environmentally advantageous. Abstract: The present study investigates the prospective of substituting inorganic medium with organic food waste compost medium as a nutrient supplement for the cultivation of Chlorella vulgaris FSP-E. Various percentages of compost mixtures were replaced in the inorganic medium to compare the algal growth and biochemical composition. The use of 25% compost mixture combination was found to yield higher biomass concentration (11.1%) and better lipid (10.1%) and protein (2.0%) content compared with microalgae cultivation in fully inorganic medium. These results exhibited the potential of combining the inorganic medium with organic food waste compost medium as an effective way to reduce the cultivation cost of microalgae and to increase the biochemical content in the cultivated microalgae.